Understanding farmers' selection criteria for rice varieties: A case in Madhya Pradesh, Eastern India - Sahu, Ram Kumar; Sahu, Vishwa Nath; Sharma, M.L.; Paris, T.R.; McAllister, Karen; Singh, Rama Kant; Sarkarung, Surapong (CGIAR Systemwide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovation, 2001)
This paper presents information from a participatory breeding project initiated in 1997 at the International Rice Research Institute (IRRI) in collaboration with plant breeders and social scientists from six national agricultural research institutions located in eastern India. The Indira Gandhi Agricultural Uni- versity (IGAU) in Raipur, Madhya Pradesh, is one of the collaborating centers. The information given here is based on a sample survey of 75 rice-farming households in three villages of the Raipur district, Madhya Pradesh. Surveys were conducted to characterize farmer’s cropping fanning systems, rice varietal diversity, degree of market orientation, gender roles, as well as socioeconomic differences, and lo relate these to farmers' rice varietal preferences. The focus is on methodologies for improving understanding of fanners' (including women farmer's) criteria for selecting specific rice varieties and how these criteria are considered in participatory breeding strategies for rain fed lowland conditions in Madhya Pradesh, eastern India.